Psycho-Philosophical Dimensions of Language Education: Mixed-Methods Exploration of Russian to Ewe Linguistic Skills Transfer - Fenuku, Samson Dodzi (Universitas Pendidikan Mandalika, 2024)
Formal education relies heavily on effective teaching methods and styles, which are particularly crucial in language education. The transfer of linguistic skills between Russian, a Slavonic language, and Ewe, a Niger-Congo language, presents a complex challenge due to their structural and cultural differences. This study delves into the complexities of transferring skills from Russian, a language from the Slavic branch of the Indo-European family, to Ewe, a language of the Niger-Congo family, focusing on the interplay between teaching methodologies, psychological factors, and philosophical perspectives. The primary objectives were to evaluate the effectiveness of various teaching methods, analyze the psychological influences on language education, and understand how philosophical viewpoints shape language teaching practices. Utilizing a mixed-methods approach, the research combined quantitative survey data from 60 participants with qualitative insights from interviews with 15 educators. The findings highlighted a preference for interactive and technology-assisted methods, with a strong emphasis on communicative techniques. The psychological assessment indicated high levels of motivation and adaptability among learners, favouring interactive and collaborative learning environments. Thematic analysis of philosophical perspectives revealed a diverse spectrum of ideologies that inform teaching practices. The study concludes that a pedagogical approach embracing interactivity, technological integration, and philosophical diversity is essential for effective language education. It calls for professional development that equips educators to employ a range of teaching methods and to effectively use technology. The research underscores the need for a learner-centred, adaptable educational paradigm that caters for diverse learner needs and preferences, advocating a more inclusive approach to language teaching.